Type 2 diabetes mellitus' impact on heart failure patients' exercise tolerance: a focus on maximal fat oxidation during exercise - Zhu, Huiying; Pan, Jianchao; Wen, Jianxuan; Dang, Xiaojing; Chen, Xiankun; Fan, Yunxiang; Lu, Weihui; Jiang, Wei (Frontiers in cardiovascular medicine, 2025)
To explore the impact of type 2 diabetes mellitus (T2DM) on exercise tolerance and fat oxidation capacity in patients with heart failure (HF). We retrospectively analyzed 108 Chinese patients with HF who were divided into a diabetic group (T2DM group, = 47) and a non-diabetic group (non-T2DM group, = 61). All subjects completed cardiopulmonary exercise testing (CPX). We determined their fat oxidation (FATox) by indirect calorimetry. In the HF patients, the peak oxygen uptake (VO ) value was 14.76 ± 3.27 ml/kg/min in the T2DM group and 17.76 ± 4.64 ml/kg/min in the non-T2DM group. After adjusting for age, sex, body mass index (BMI), log N-terminal pro-B type natriuretic peptide (log NT-proBNP), left ventricular ejection fraction (LVEF), hemoglobin, renal function, coronary heart disease and hypertension, the peak VO was lower in the T2DM group compared to the non-T2DM group with a mean difference (MD) of -2.0 ml/kg/min [95% confidence interval (CI), -3.18 to -0.82, < 0.01]. The VO at anaerobic threshold (AT VO ) was also lower in the T2DM group than in the non-T2DM group, with a MD of -1.11 ml/kg/min (95% CI -2.04 to -0.18, < 0.05). Regarding the fat oxidation capacity during CPX, the T2DM group's maximal fat oxidation (MFO) was lower than that of the non-T2DM group (0.143 ± 0.055 vs. 0.169 ± 0.061 g/min, < 0.05). In addition, the T2DM group had lower FATox at exercise intensity levels of 40% ( < 0.05) and 50% ( < 0.05) of peak VO , compared to the non-T2DM group. T2DM is associated with a decrease in exercise tolerance and fat oxidation capacity in patients with heart failure. Thus, it could be useful to develop exercises of appropriate intensity to optimize physical and metabolic health.